Perforated proximal jejunal gastrointestinal stromal tumor pT4N0M0 presenting with severe sepsis: A case report and literature review. (September 2020) - Meneses, Evander; Elkbuli, Adel; Baroutjian, Amanda; McKenney, Mark; Boneva, Dessy
Abstract: Introduction: Gastrointestinal stromal tumors (GISTs) are mesenchymal tumors that occur along the alimentary tract, and are most commonly found in the stomach. Rarely, these tumors can occur in the small bowel, and when located in the duodenum or proximal jejunum, they may require challenging reconstruction of the alimentary tract. Patients with GISTs often present with non-specific abdominal pain or symptoms of obstruction, hemorrhage, and less commonly perforation. Presentation of case: A 46-year-old male presented to the hospital with a one-day history of left upper quadrant pain with fevers and chills. Physical examination was significant for signs of peritonitis, and laboratory results revealed leukocytosis and lactic acidosis. CT abdomen showed a large soft tissue mass in the proximal jejunum. In the operating theater he was found to have a perforated jejunal tumor. Pathology report revealed a 13cm GIST, pT4N0M0, Stage IIIa. He had an uneventful recovery and was discharged nine days after surgery. Discussion: Proximal jejunal GISTs are a rare entity and when present, perforation is unlikely. Pathological diagnosis of GISTs are relies on immunohistochemistry demonstrating c-KIT or CD34 positivity. The prognosis of GISTs are dependent on the size and the mitotic index. Definitive treatment of non-metastatic GISTs is R0 resection. When located in the duodenum or proximal jejunum, resection can be very challenging and may require clinical expertise in order to safely perform complex alimentary tract reconstruction. Conclusion: Further investigation is required in order to determine best practice management for patients who present with proximal GISTs. Highlights: A rare presentation of proximal jejunal GIST as a necrotic perforated mass causing severe sepsis. Successful treatment of a pT4N0M0 (Stage IIIa) proximal jejunal GIST in the emergency setting with an uneventful hospital recovery. R0 resection of the proximal jejunal GIST with hand-sewn end-to-side anastomosis.